Electron structure and electron-phonon interaction in the strongly correlated electron system of cuprates: Strong Correlations - Ovchinnikov, S.G.; Gavrichkov, V.A.; Korshunov, M.M.; Shneyder, E.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The generalized tight-binding method presents a practical realization of the scheme that describes quasiparticles in strongly correlated electron system and consists of exact intra-cell diagonalization of the model Hamiltonian and perturbative treatment of the inter-cell hoppings. In present paper this method and its ab initio modification applied to undoped and weakly doped HTSC cuprates. Results are in very good agreement with the experimental ARPES data on various compounds. Starting with multiband p—d model the realistic effective low-energy Hamiltonian ofstrongly correlated electrons interacting with spin fluctuations and phonons is derived both for hole and electron doped systems. Without electron—phonon interaction the pure magnetic mechanism of pairing does not provide the correct value of Tc even for single-layer La2–xSrxCuO4 andNd2–xCexCuO4.